Evolution of the turnover of state-owned agricultural real estate in Poland after 1989 - Czechowski, Paweł; Niewiadomski, Adam (Przegląd Prawa Rolnego, 2022)
The article presents the main stages of the evolution of the transactions involving agricultural real estate in Poland after 1989. The focus is on the basic legal instruments applicable to ownership transformation. The evolution of the functions of legal entities dealing with agricultural real estate trading in Poland has also been assessed. Various possibilities of shaping the model of Polish agriculture have been proposed, depending on the adopted rules of managing state property, including privatisation or lease. Finally, the impact of public authorities on the trading in private agricultural real estate has been assessed in the context of European regulations.